Growth of Global Corporate Debt : Main Facts and Policy Challenges - Abraham, Facundo; Cortina, Juan J.; Schmukler, Sergio L. (World Bank, Washington, DC, 2020)
This paper surveys the literature to document the main stylized facts, risks, and policy challenges related to the expansion of global nonfinancial corporate debt after the 2008–09 global financial crisis. Nonfinancial corporate debt steadily increased after the crisis, especially in emerging economies. Between 2008 and 2018, corporate debt increased from 56 to 96 percent of gross domestic product in emerging economies, whereas this ratio remained stable in developed economies. Nonfinancial corporate debt was mainly issued through bond markets, and its growth can be largely attributed to accommodative monetary policies in developed economies. Whereas increased debt financing has some positive aspects, it has also amplified firms' solvency risks and exposure to changes in market conditions, such as the economic downturn triggered by the COVID-19 pandemic. Because capital markets have a larger role in firm financing, policy makers have limited tools to mitigate the risks of growing firm debt.